Exploring Collection of Sign Language Datasets: Privacy, Participation, and Model Performance - Bragg, Danielle; Koller, Oscar; Caselli, Naomi; Thies, Bill (ASSETS 2020, 2020)
As machine learning algorithms continue to improve, collecting training data becomes increasingly valuable. At the same time, increased focus on data collection may introduce compounding privacy concerns. Accessibility projects in particular may put vulnerable populations at risk, as disability status is sensitive, and collecting data from small populations limits anonymity. To help address privacy concerns while maintaining algorithmic performance on machine learning tasks, we propose privacy-enhancing distortions of training datasets. We explore this idea through the lens of sign language video collection, which is crucial for advancing sign language recognition and translation. We present a web study exploring signers' concerns in contributing to video corpora and their attitudes about using filters, and a computer vision experiment exploring sign language recognition performance with filtered data. Our results suggest that privacy concerns may exist in contributing to sign language corpora, that filters (especially expressive avatars and blurred faces) may impact willingness to participate, and that training on more filtered data may boost recognition accuracy in some cases.